Enhancing the oxidation of polystyrene through a homogeneous liquid degradation system for effective microbial degradation - Hong Rae Kim; Hye Yeon Koh; Hyeyoung Shin; Dong-Eun Suh; Sukkyoo Lee; Donggeon Choi (Frontiers in Microbiology)
Plastics play a crucial role in modern industries; however, their resistance to natural degradation contributes to environmental pollution, and microplastics pose a health threat. The hydrophobic nature of microplastics poses a considerable challenge, rendering them resistant to dissolving in water. In this study, we conducted a comparative analysis of the microbial biodegradation capabilities of polystyrene in solid and liquid states. Polystyrene in its solid foam form, along with polystyrene converted into a liquid state using ethyl-ester oil, was biodegraded by microorganisms. Subsequently, the liquid plastic was re-extracted into its solid form, and the degree of degradation was assessed using weight loss measurement, XPS, FT-IR, GPC, and TGA. Liquid-state polystyrene exhibited a higher degradation rate than that reported previously. Furthermore, liquid polystyrene undergoes more pronounced oxidation than its solid counterpart, leading to an increased oxygen atom ratio. Chemical structure analysis highlighted the distinct formation of –OH and C=O functional groups in the liquid state compared to those in the solid state. Additionally, notable changes in the molecular weight and thermal stability of polystyrene were observed during biodegradation in the liquid state. This study suggests that a heterogeneous reaction (solid plastic-liquid medium) might impede plastic biodegradation, while indicating the potential to enhance the degradation efficiency through a homogeneous reaction (liquid plastic-liquid medium). The follow-up study identifies appropriate solvents and optimizes cultivation conditions, offering potential to enhance the efficiency of biological plastic degradation.